De reforma em reforma: as recomendações dos organismos internacionais para a organização do ensino médio - Muniz, Tatiana Ludmila Santos Brandao [UNIFESP] (2020)
Brazilian public policies on secondary education have undergone constant changes in recent decades, with emphasis on projects undertaken since the 1990s; High School for Life in 1998, High School in 2011 and New High School in 2017. We are interested in this research to investigate the international recommendations that impacted on the conduct of policies aimed at this level of education that, in different ways, impacted different countries in Latin America; therefore, the objective of this work is to identify and discuss the speeches, guidelines and prescriptions contained in documents from two international organizations, the World Bank (BM) and the United Nations Educational, Scientific and Cultural Organization (UNESCO) , about high school. To carry out the investigation, the methodological procedure adopted was the documentary analysis, using, for this purpose, the documents produced by these organizations. For the work with the documentary corpus, and according to Bardin (1977), we use lexicology as a technique to carry out documentary analysis, since the focus of content analysis is the word and its semantic and metaphorical field; likewise, we observe the recommendations of SHIROMA, E. O., CAMPOS, R. F. and GARCIA, R. M. (2005) for documentary analysis. As an analytical resource, we adopted the policy approach cycle, proposed by Stephen Ball and Richard Bowe (1992), with emphasis on the dimensions related to the context of influence of the policy discourse, which allowed us to specifically assess the prescriptions of international organizations related to high school. The investigation allowed us to conclude that the guidelines of international organizations direct educational reforms to the economic interests of the capital system, antagonizing in some orientations of their policies with other texts of educational research that are supported in sciences other than economics, such as sociology, psychology and history.